NATIONAL-CULTURAL CODES AS SEMIOTIC CONSTRUCTS IN GAFUR GHULAM’S “SHUM BOLA” - Berdiyeva Sitora Utkerovna (International Journal of Literature and Language Studies, 2026)
Abstract. In Gafur Ghulam’s Shum bola, national-cultural codes constitute a complex semiotic system that embodies the historical memory, cultural values, everyday practices, and collective worldview of the Uzbek people. Functioning as culturally marked signs, these codes facilitate the transmission of nationally specific meanings and contribute to the construction of the text’s linguocultural space. Within the narrative, they serve as a significant mechanism for the creation of humor, generating multilayered semantic and pragmatic effects that are deeply rooted in the source culture. Consequently, the translation of such codes necessitates various transcultural and interpretative strategies to preserve their communicative and aesthetic functions. In this regard, humor in “Shum bola” should be viewed not merely as a literary device for entertainment but as a semiotic manifestation of national identity, reflecting the cultural consciousness and value system of Uzbek society.